'Left behind' North of the Border? Economic Disadvantage and Intersectional Inequalities in Post-Pandemic Scotland. Issue 4 (September 2022) - Morrison, James
Abstract : UK media and political discourse has increasingly been dominated by concerns about the economic disadvantages experienced by post-industrial communities collectively labelled 'left behind' – and the deepening cultural fault-lines between them and wider society recent democratic events are said to have exposed. An overlapping narrative has re-cast many such communities as 'red-wall'/'blue-wall' constituencies, following the 2016 Brexit referendum and subsequent general elections – leading to a growing political focus on 'levelling up' infrastructural investment, employment and training opportunities to address economic inequalities between South-East England and much of the rest of the UK. To date, though, the primary political focus of these discourses has been on areas of northern and eastern England, the Midlands and Wales, with only a handful of contributions to the debate emphasizing the plight of comparably 'left-behind' areas of Scotland – notably an Institute for Fiscal Studies (IFS) report highlighting COVID-19's disproportionate economic impact on Scottish cities like Glasgow and Dundee with significant pockets of poverty (Davenport & Zaranko, 2020 ). This article draws on interviews with people from a range of disadvantaged groups in Scotland to explore how communities that have often been left out of the 'national conversation' about the 'left behind' are both experiencing economic inequality and starting to fight back – through incipient forms of grassroots 'DIY levelling up'.